Penerapan Restorative Justice terhadap Pelaku Tindak Pidana Penganiayaan Ringan di Kejaksaan Negeri Semarang - Lilis Rahmawati; Safik Faozi (UNES Law Review, 2023)
Emergence of Restorative Justice as a criticism of the implementation process in the criminal justice system, which has been viewed as ineffectual in resolving problems in people's lives. Restorative Justice is a procedural approach to settling criminal cases that entails the active involvement of individuals responsible for the offense, victims, relatives of both perpetrators and victims, as well as other pertinent stakeholders. The primary objective of this approach is to achieve a fair resolution by prioritizing the restoration of the affected parties to their original state, rather than focusing solely on retaliation. This research will analyze and explain how Restorative Justice is implemented against persecutors of the crime of persecution at the Semarang District Attorney, as well as what the obstacles in its implementation. This study employs a normative juridical research type with in concreto research specifications, secondary data gathered from library materials, and a qualitative data analysis methods. The results of the study show (1) Because the prosecution complied with the conditions of article 5 of Prosecutor's Regulation No. 15 of 2020 regarding Termination of Prosecution, Restorative Justice may no longer be applied to those who committed the crime of persecution at the Semarang District Attorney's Office. According to restorative justice, a first-time offender is subject to punishment under Article 351 for crimes and criminal acts of persecution (1) of the Criminal Code, as well as for the implementation mechanism through several stages beginning with stage two, peace efforts, peace process regulated in Article 7 to Article 12 until the prosecution is terminated with the issuance of a Decission Letter on Termination of Prosecution.(2) here are no obstacles in the application of Restorative Justice due to the interrelation of legal structure, legal substance and legal culture.